Pengaruh Pemberian Pelvic Floor Exercise TerhadapEnuresis Pada Anak Pre-Sekolah (Di Sekolah Luar Biasa Negeri Gedangan Sidoarjo) - Satria Aji Dewantara; Nurul Halimah; Angria Pradita; Achmad Fariz (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
: Enuresis is bedwetting behavior that occurs in children aged at least 5 years or more which is caused by delays in the development of the urinary organs and supported by weakness of the pelvic floor muscles which eventually causes children to have bed wetting behavior during the day or especially at night. Â Pelvic Floor Exercise is a pelvic floor muscle exercise which is quite common and is widely used in cases of incontinence, whereby activating the pelvic floor muscles isometrically and its muscle control is expected to increase sensorimotor so that it has an impact on the appearance of a feeling when the bladder response is full and holding it for a while so it doesn't automatically proceeds to the excretion process of urination. Methods: Â The design of this study uses pre-experimental. The type of research is one group pretest posttest. In this study, it was started by conducting interviews with parents and explaining filling in the Bladder Diary sheet which is useful for knowing the frequency of enuresis in children. The study was conducted with 15 respondents, giving pelvic floor exercise 2 times a week within 8 weeks.Results: Â Showing the result of the significance value of the Paired Sample T Test is 0.000<Î± (Î±= 0.005), then there is an effect of giving Pelvic Floor Exercise on changes in Bladder Diary resultsConclusion: There is an effect after giving the Pelvic Floor Exercise to the frequency of enuresis in pre-school-aged children at the SLB Negeri Gedangan Sidoarjo, with a Paired T-Test significance of 0.000 < Î± (Î± = 0.05). Where with these results it can be reduced to eliminate the habit of wetting the bed at night in children.